The Japanese main bank system: (Clarendon Press, 1994)
this book also examines the relevance of the system as a model for developing market economies and transforming socialist economies the world over. The basic characteristics of the main bank system are examined here: its roots, development, and role in the heyday of its rapid growth, as well as its performance, strengths and weaknesses